Pemahaman Nilai-Nilai Dalihan Natolu Dalam Budaya Batak Toba dan Implementasinya Dalam Hidup Beriman Katolik - Alex Kardo Simamora; Megawati Naibaho; Antonius Sipahutar (Journal New Light, 2024)
Dalihan Natolu is the basic philosophy of life for the Toba Batak tribe which is contained in three elements, namely respect, veneration and support. This unity cannot be separated from the life of the Toba Batak tribe. Dalihan Natolu's kinship system, namely somba marhula-hula (respect to uncle's family), manat mardongan tubu (being careful to siblings), and elek marboru (graciousness to our sisters), is a communal foundation that is closely related to each other. Each component in Dalihan Natolu is implemented according to their respective positions and roles. The values that exist in Dalihan Natolu have a correlation with the Catholic faith, namely theological virtues (faith, hope, and love) and cardinal virtues (prudence, justice, fortitude, and temperance).Theological and cardinal virtues are virtues that animate everyone to live Christian morals. Likewise, with the Dalihan Natolu values it can be understood that Christian morals are not just law implementation, but a response to God's call. Everyone's way and pattern of life must be adapted with the teachings of God. Thus, every person from any culture is able to reach the ultimate goal offered by God which is genuine happiness